FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN PAJAK PENGHASILAN BADAN PADA KANTOR PELAYANAN PAJAK DI KOTA BANJARMASIN - Aris Setia Noor; Berta Lestari (Faculty of Economics and Business, Universitas Malikussaleh, 2018)
The purpose of this study are: (1) To find out how much the influence of tax climateon the receipt of corporate income tax partially, (2) To find out how much influencethe tax climate on corporate income tax revenue together. The research methodused is survey research method. Data collection techniques used the census method.Data collection is done through direct observation to the object of research and literature study. The method of analysis used in this study is Path Analysis. Based ondata used the statistic analistic shows that: (1) Simultaneously to fulfill and conveyclearly and accurately the tax form, to account correctly the debt tax, to pay the debttax at the right time give positive and significant to 5% real standard toward the acceptance of income tax body. (2) Partially to fulfill and convey clearly and accuratelythe tax form, to account correctly the debt tax, to pay the debt tax at the right timegive positive and insignificant to 5 % real standard toward the acceptance of incometax body.The result of this research shows that other unaccounted variable has verysmall affect in the amount of 0.32% toward acceptance of income tax body.